2022
DOI: 10.3389/fmed.2022.878337
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Risk Factors for New Dependency on Chronic Care, Respiratory Support, Dialysis and Mortality in the First Year After Sepsis

Abstract: Sepsis survival is associated with adverse outcomes. Knowledge about risk factors for adverse outcomes is lacking. We performed a population-based cohort study of 116,507 survivors of hospital-treated sepsis identified in health claims data of a German health insurance provider. We determined the development and risk factors for long-term adverse events: new dependency on chronic care, chronic dialysis, long-term respiratory support, and 12-month mortality. At-risk patients were defined by absence of these con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In contrast to the high case fatality rate in Latvian hospitals, the observed 12% one-year mortality rate for sepsis survivors is relatively low. For comparison, studies focusing on one-year mortality rates for patients discharged after an initial sepsis hospitalization report figures such as 12.5% [40], 15% [41], 22.3% [42], 23% [43], and even as high as 30.7% [37,44]. Furthermore, a meta-analysis indicates a post-acute sepsis mortality rate of 16.1% at one year, derived by estimating the difference between cumulative one-year mortality and acute mortality across 43 studies that did not specifically focus on this outcome [45].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the high case fatality rate in Latvian hospitals, the observed 12% one-year mortality rate for sepsis survivors is relatively low. For comparison, studies focusing on one-year mortality rates for patients discharged after an initial sepsis hospitalization report figures such as 12.5% [40], 15% [41], 22.3% [42], 23% [43], and even as high as 30.7% [37,44]. Furthermore, a meta-analysis indicates a post-acute sepsis mortality rate of 16.1% at one year, derived by estimating the difference between cumulative one-year mortality and acute mortality across 43 studies that did not specifically focus on this outcome [45].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with sepsis often have compromised host immune responses that are characterized by lymphopenia [48,49]; in 25% of sepsis patients who were readmitted with sepsis, the same pathogen was isolated, and a previous gram-negative bacteremia and/or samesite infection predisposed to recurrence of sepsis that was caused by the same pathogen [29]. In addition, nosocomial and multidrug-resistant infections increase the odds of respiratory support and are associated with an increased 12-month mortality risk [50]. Furthermore, our study demonstrated that survivors who had PICS 3 months after sepsis showed a lower number of lymphocytes, and a higher detection rate of MRSA-and ESBL-producing bacteria and fungi in blood cultures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 31.5% of survivors with no prior need for care had new care needs [ 16 ]. In particular, pre-existing comorbidities increased the risk for adverse outcomes after sepsis [ 17 ]. Long-term mortality in the first 12 months after discharge was 30.7% [ 16 ].…”
Section: Burden Of Sepsis Is Not Only About Acute Illnessmentioning
confidence: 99%